ANALYSIS OF CONTENT VALIDITY IN ENGLISH EXAMINATION TEST ON PUBLIC HEALTH’S STUDENTS - Astuti, Peni (AGUSPATI Research Institute, 2020)
The objective of this research is to find out the empirical evidence of the English examination test content validity made by the English lecturer for the even semester of the first grade of Public Health’s students administered at the University of Faletehan Serang. The total number of the test items was 70 items. In this study, the writer used qualitative research in which the writer collected data by asking the English final paper test and syllabus to the lecturer. Then the writer analyzed the test items, whether the final test has content validity. This study has not done yet in this institution. Also, this study is categorized as descriptive analysis in which to describe the conformity and in-conformity of the Public Healths’s English summative test with the syllabus and learning achievement. The instrument of this study was the final English test of the Public Health Department in the first semester of the first grade in the 2019/2020 academic year. The respondent used was 112 students.